An economical Nanopore sequencing assay for human papillomavirus (HPV) genotyping - Wai Sing Chan; Tsun Leung Chan; Chun Hang Au; Chin Pang Leung; Man Yan To; Man Kin Ng; Sau Man Leung; May Kwok Mei Chan; Edmond Shiu Kwan Ma; Bone Siu Fai Tang (BMC, 2020)
Abstract Background Human papillomavirus (HPV) testing has been employed by several European countries to augment cytology-based cervical screening programs. A number of research groups have demonstrated potential utility of next-generation sequencing (NGS) for HPV genotyping, with comparable performance and broader detection spectrum than current gold standards. Nevertheless, most of these NGS platforms may not be the best choice for medium sample throughput and laboratories with less resources and space. In light of this, we developed a Nanopore sequencing assay for HPV genotyping and compared its performance with cobas HPV Test and Roche Linear Array HPV Genotyping Test (LA). Methods Two hundred and one cervicovaginal swabs were routinely tested for Papanicolaou smear, cobas HPV Test and LA. Residual DNA was used for Nanopore protocol after routine testing. Briefly, HPV L1 region was amplified using PGMY and MGP primers, and PCR-positive specimens were sequenced on MinION flow cells (R9.4.1). Data generated in first 2 h were aligned with reference sequences from Papillomavirus Episteme database for genotyping. Results Nanopore detected 96 HPV-positive (47.76%) and 95 HPV-negative (47.26%) specimens, with 10 lacking β-globin band and not further analyzed (4.98%). Substantial agreement was achieved with cobas HPV Test and LA (κ: 0.83-0.93). In particular, Nanopore appeared to be more sensitive than cobas HPV Test for HPV 52 (n = 7). For LA, Nanopore revealed higher concordance for high-risk (κ: 0.93) than non-high risk types (κ: 0.83), and with similar high-risk positivity in each cytology grading. Nanopore also provided better resolution for HPV 52 in 3 specimens co-infected with HPV 33 or 58, and for HPV 87 which was identified as HPV 84 by LA. Interestingly, Nanopore identified 5 additional HPV types, with an unexpected high incidence of HPV 90 (n = 12) which was reported in North America and Belgium but not in Hong Kong. Conclusions We developed a Nanopore workflow for HPV genotyping which was economical (about USD 50.77 per patient specimen for 24-plex runs), and with comparable or better performance than 2 reference methods in the market. Future prospective study with larger sample size is warranted to further evaluate test performance and streamline the protocol.